2014
DOI: 10.3892/ijo.2014.2511
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Yin Yang 1 in bone marrow-derived human multiple myeloma and its clinical significance

Abstract: Multiple myeloma (MM) patients initially respond to conventional therapy, however, many develop resistance and have recurrences. We have reported in other tumors that the transcription factor Yin Yang 1 (YY1) is a resistant factor and, thus, we hypothesized that YY1 may be over-expressed in MM. Significantly, higher expression (staining intensity and cell frequency) of YY1 in MM cell lines and in bone marrow-derived (BM) MM from 22 MM patients was observed as compared to expression in normal BM. Higher nuclear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 37 publications
(39 reference statements)
3
14
0
Order By: Relevance
“…Evidence provided by us and others support a critical role of the multifunctional transcription factor YY1 in oncogenesis . YY1 overexpression detected in CRC and several other solid and hematological malignancies is linked to tumor growth, proliferation, migration, and metastasis . Consistent with previous reports indicating a significant decrease in overall survival of CRC patients with high YY1 protein levels, our present findings show a clinical association among high YY1 mRNA expression, advanced tumor grade and high risk for distant metastasis; suggesting that YY1 may serve as an independent prognostic biomarker for CRC patients.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Evidence provided by us and others support a critical role of the multifunctional transcription factor YY1 in oncogenesis . YY1 overexpression detected in CRC and several other solid and hematological malignancies is linked to tumor growth, proliferation, migration, and metastasis . Consistent with previous reports indicating a significant decrease in overall survival of CRC patients with high YY1 protein levels, our present findings show a clinical association among high YY1 mRNA expression, advanced tumor grade and high risk for distant metastasis; suggesting that YY1 may serve as an independent prognostic biomarker for CRC patients.…”
Section: Discussionsupporting
confidence: 91%
“…23,32 YY1 overexpression detected in CRC and several other solid and hematological malignancies is linked to tumor growth, proliferation, migration, and metastasis. [33][34][35][36][37][38][39] Consistent with previous reports indicating a significant decrease in overall survival of CRC patients with high YY1 protein levels, 25 our present findings show a clinical association among high YY1 mRNA expression, advanced tumor grade and high risk for distant metastasis; suggesting that YY1 may serve as an independent prognostic biomarker for CRC patients. On the same context, we have previously identified the critical role of YY1 as a mediator of tumor resistance to both chemo-and immunomediated apoptosis in various cancer models.…”
Section: Discussionsupporting
confidence: 91%
“…The report by Potluri et al (2013) demonstrated that YY1 is overexpressed in most MM derived from patients, that YY1 is localized in the nucleus, and that there was a correlation with the repression of Bim. Their findings were confirmed by Huerta-Yepez et al (2014). The depletion of YY1 and RelA resulted in the upregulation of Bim levels and induction of apoptosis.…”
Section: Yin Yang 1 Protein Expression Levelssupporting
confidence: 65%
“…Because YY1 is overexpressed in many cancers, YY1 is considered to be a potential novel prognostic marker and therapeutic target [4042]. However, as data on its prognostic significance has become available for more human cancers, YY1′s role in tumor progression has become more controversial [32].…”
Section: Discussionmentioning
confidence: 99%